Association of APOL1 renal disease risk alleles with Trypanosoma brucei rhodesiense infection outcomes in the northern part of Malawi. - Kelita Kamoto; Harry Noyes; Peter Nambala; Edward Senga; Janelisa Musaya; Benjamin Kumwenda; Bruno Bucheton; Annette Macleod; Anneli Cooper; Caroline Clucas; Christiane Herz-Fowler; Enock Matove; et al. (Public Library of Science (PLoS), 2019)
Trypanosoma brucei (T.b.) rhodesiense is the cause of the acute form of human African trypanosomiasis (HAT) in eastern and southern African countries. There is some evidence that there is diversity in the disease progression of T.b. rhodesiense in different countries. HAT in Malawi is associated with a chronic haemo-lymphatic stage infection compared to other countries, such as Uganda, where the disease is acute with more marked neurological impairment. This has raised the question of the role of host genetic factors in infection outcomes. A candidate gene association study was conducted in the northern region of Malawi. This was a case-control study involving 202 subjects, 70 cases and 132 controls. All individuals were from one area; born in the area and had been exposed to the risk of infection since birth. Ninety-six markers were genotyped from 17 genes: IL10, IL8, IL4, HLA-G, TNFA, IL6, IFNG, MIF, APOL, HLA-A, IL1B, IL4R, IL12B, IL12R, HP, HPR, and CFH. There was a strong significant association with APOL1 G2 allele (p = 0.0000105, OR = 0.14, CI95 = [0.05-0.41], BONF = 0.00068) indicating that carriers of the G2 allele were protected against T.b. rhodesiense HAT. SNP rs2069845 in IL6 had raw p < 0.05, but did not remain significant after Bonferroni correction. There were no associations found with the other 15 candidate genes. Our finding confirms results from other studies that the G2 variant of APOL1 is associated with protection against T.b. rhodesiense HAT.